The relevance of affordance for women "ageing in place" - McKenzie, Fiona Haslam; Jefferson, Therese (Women in Social and Economic Research, 2007)
Affordance is a separate and distinct concept from affordability and is infrequently used in discussions of housing and ageing. It is nonetheless a concept that can provide a cohesive framework for the consideration of wide-ranging socio-cultural benefits thatderive from features of the built environment.Affordance is a term coined in ecological psychology by Gibson (1979). One of the key aspects of Gibson's idea of affordance is its contrast with theories and concepts that rely solely on human perceptions as important in determining the way objects are used.That is, affordances are features of the environment that, given the capacities of a particular agent, facilitate particular actions. For example a doorway affords movement across a threshold. An important fact about affordances is that while they are in a senseobjective, real and physical, unlike values and meanings, they are neither an objective property nor a subjective property. They are both a fact of the environment and a fact of embodied behaviour that exists only in the relation between them.The inter-relationship of the affordance of housing as people age and a property's affordability to enhance affordance has not been considered by policy makers. Nor have the concepts been considered from a gendered perspective. This paper will examinethe potential benefits of applying the concept of affordance to studies of housing and the government policies encouraging 'ageing in place'. It will also consider the interrelationships between affordance and affordability, particularly for 'middlessent'women who are contemplating 'ageing in place'.